Anaerobic co-digestion (ACD) of glycerin pitch (GP) with oleochemical effluent (OCE) - Chow, Wei Ling (2019)
Glycerin pitch (GP) with an average chemical oxygen demand (COD) of 973,750 mg/L produced from the oleo chemical industries have raised serious disposal problem. GP is the waste collected at the bottom of a distillation column that purifies crude glycerin. In some plants, this waste is mixed with 30% oleo chemical effluent (OCE) before treatment. Costly incineration or slow dosing of GP into conventional wastewater treatment plants are the only currently available treatment methods for GP. No study has been reported on using GP as co-substrate in anaerobic co-digestion (ACD) with OCE in addressing the disposal problem which formed the novelty of this study. Therefore, the aim of this research is to develop a cost effective ACD of GP with OCE. The research conducted including feasibility study, comparison study of ACD of GP with OCE at different digestion ratios, different reactor configurations and pre-treatment of substrate. The results revealed that continuous stirred tank reactor (CSTR) at an organic loading rate of (OLR) 4 g COD/L.day is chosen as the best option for co-digestion of GP with OCE treatment due to its great enhancement in the reduction of COD, oil and grease (O&G) and other parameters. COD removal of 70% is reported as the maximum degradation efficiency. The excellent performance is well beyond the target set >50% COD removal by the industry. It is concluded that GP as ACD substrate represents a cost-effective alternative to the current waste management technology.